Answer:
2Al(s) + 3Fe⁺²(Aq) → 2Al⁺³(aq) + 3Fe(s)
Explanation:
The shorthand notation first places the oxidation reaction and then the reduction reaction. So, the half-reactions are:
Al(s) → Al⁺³(aq) + 3e⁻ (Al must lose 3 electrons)
Fe⁺²(Aq) + 2e⁻ → Fe (s) (Fe⁺² must gain 2 electrons)
The total amount of electrons must be equal, so the first equation must be multiplied by 2, and the second by 3:
2Al(s) → 2Al⁺³(aq) + 6e⁻
3Fe⁺²(Aq) + 6e⁻ → 3Fe (s)
And now they must be summed, which will be the balanced chemical equation:
2Al(s) + 3Fe⁺²(Aq) → 2Al⁺³(aq) + 3Fe(s)